(untitled) (Journal of Institute of Science and Technology, 2017)
Copper oxide (CuO) nanoadditives were successfully synthesized in laboratory by precipitation technique. X-ray diffraction spectroscopy (XRD) showed the crystalline nature of CuO with the average crystal size of 10 nm. The prepared CuO has been blended with engine oil. Thus prepared modified engine oil showed good kinematic viscosity 158 cSt and 19.06 cSt at 40⁰C and 100⁰C respectively. The viscosity index was also found to be improved to 122. Similarly, the pour point was also found to be considerably decreased to -27⁰C which is due to presence of CuO that acts as good pour point depressant. The flash point of modified engine oil reached to 225⁰C. In addition, modified engine oil was found to be reluctant towards water and it does not contain noticeable amount of water and found to be noncorrosive in nature having copper strip corrosion rating 1b according to ASTM D-130 method. Results revealed that the physio-chemical parameters of engine oil could be improved by the addition of CuO nanoadditive. Journal of Institute of Science and Technology Volume 22, Issue 1, July 2017, page: 152-158